Menjadi Muslim Milenial di Media Sosial: Analisis Netnografi pada Makna Gaya Hidup Halal bagi Komunitas Muda di Pekanbaru - Trisakti, Febby Amelia (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
This study aims to find out and analyze the identification of millennial Muslims on social media and the coverage formed regarding the halal lifestyle for millennial Muslims in Pekanbaru. How topics trend, top search keywords, preferred content and identify Muslim millennials. This study used the nethnography method to analyze the interactions and conversations in online social media communities. The results showed that the top hashtags used were #dakwahmilenial and #Halalismyway. In addition, halal lifestyle is interpreted on social media through several categorizations such as Halal Culinary Content, Halal Recipes and Cuisine, Halal Product Advertising, Religious Education Content, Halal Lifestyle and Fashion, Halal Social and Awareness Campaigns, Online Communities, and Product Reviews and Places to Eat. They make social media a religious